Soft x-ray high order harmonic generation driven by high repetition rate ultrafast thulium-doped fiber lasers - Gebhardt, Martin; Heuermann, Tobias; Wang, Ziyao; Lenski, Mathias; Gaida, Christian; Klas, Robert; Kirsche, Alexander; Haedrich, Steffen; Rothhardt, Jan; Limpert, Jens (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
Intense, ultrafast laser sources with an emission wavelength beyond the well-established near-IR are important tools for exploiting the wavelength scaling laws of strong-field, light-matter interactions. In particular, such laser systems enable high photon energy cut-off HHG up to, and even beyond, the water window thus enabling a plethora of subsequent experiments. Ultrafast thulium-doped fiber laser systems (providing a broad amplification bandwidth in the 2 μm wavelength region) represent a promising, average-power scalable laser concept in this regard. These lasers already deliver ∼100 fs pulses with multi-GW peak power at hundreds of kHz repetition rate. In this work, we show that combining ultrafast thulium-doped fiber CPA systems with hollow-core fiber based nonlinear pulse compression is a promising approach to realize high photon energy cut-off HHG drivers. Herein, we show that thulium-doped, fiber-laser-driven HHG in argon can access the highly interesting spectral region around 90 eV. Additionally, we show the first water window high-order harmonic generation experiment driven by a high repetition rate, thulium-doped fiber laser system. In this proof of principle demonstration, a photon energy cut-off of approximately 400 eV has been achieved, together with a photon flux <105 ph/s/eV at 300 eV. These results emphasize the great potential of exploiting the HHG wavelength scaling laws with 2 μm fiber laser technology. Improvements of the HHG efficiency, the overall HHG yield and further laser performance enhancements will be the subject of our future work.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Fiber laser; High harmonic generation; Mid-IR laser; Nonlinear pulse compression